Pregnancy outcome of preterm caesarean delivery at two university teaching hospitals in Southern Nigeria - Alegbeleye, Justina O.; John, Dickson H.; Orazulike, Ngozi C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preterm birth has been associated with poor neonatal outcomes, particularly in resource-limited countries where managing extreme preterm newborns remains a herculean task. The objective was to determine the pattern, maternal and perinatal outcome of preterm caesarean sections. Methods: A retrospective cross-sectional study of preterm caesarean deliveries between January 1, 2010, and December 31, 2019, at the obstetric units of the University of Port Harcourt Teaching Hospital and the Rivers State University Teaching Hospital, Nigeria. SPSS 25 was used to analyze data obtained from the theatre records and case notes of the patients. Results: Most, 377 (45.92%) of the caesarean sections were performed between 35 weeks and 36 weeks and 6 days. The preterm caesarean delivery rate was 1.62%. Majority, 708 (85.92%) were done as emergencies, mostly in booked patients 452 (59.4%). Severe pre-eclampsia was the most common 265 (24.02%) indication for preterm caesarean delivery. The average hospital stay was 6.15±2.34 days, with a maternal mortality ratio of 20.6/1,000 live births. Many 771 (93.34%) of the babies were live births, with most 515 (62.35%) weighing 1.5-2.49 kg at birth. The most common neonatal complications were low birth weight 316 (21.32%) and birth asphyxia 141 (11.56%), with a perinatal mortality ratio of 66.2/1000 live births. Conclusions: Concerted efforts should be made to minimize complications associated with preterm births, through antenatal care and early identification of women at risk.